2004
DOI: 10.1093/bja/aeh088
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phenylephrine infusion regimens for maintaining maternal blood pressure during spinal anaesthesia for Caesarean section †

Abstract: For optimal management, phenylephrine should be titrated to maintain maternal BP at near-baseline values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(89 citation statements)
references
References 15 publications
5
72
3
Order By: Relevance
“…Our findings are consistent with recent published data on management of maternal hypotension during spinal anesthesia [9][10][11][12][13][14][15][16][17][18] . Mercier FJ et al, 2007 16 analysed the different preventive and curative strategies for management of hypotension during spinal anaesthesia for cesarean section.…”
Section: Resultssupporting
confidence: 93%
“…Our findings are consistent with recent published data on management of maternal hypotension during spinal anesthesia [9][10][11][12][13][14][15][16][17][18] . Mercier FJ et al, 2007 16 analysed the different preventive and curative strategies for management of hypotension during spinal anaesthesia for cesarean section.…”
Section: Resultssupporting
confidence: 93%
“…Our analyses pointed out that some obstetric factors such as the usage of oxytocin and forceps may be associated with nausea and vomiting which are common during delivery. Studies showed that the occurance of nausea and vomiting is correlated to the degree of hypotension [36]. Higher doses of oxytocin or forceps delivery may lead to sudden haemodynamic change.…”
Section: Discussionmentioning
confidence: 99%
“…[10] The prediction of obstetric spinal hypotension has received considerable attention and has recently been the subject of review in a local journal. [11] While a number of practical predictors such as body mass index, maternal age and baseline heart rate have shown potential, results have been conflicting and applied predominantly to elective patients.…”
Section: Prediction Of Obstetric Spinal Hypotensionmentioning
confidence: 99%
“…Initial work using high phenylephrine infusion rates (100 µg/min) and aggressive fluid coloading showed that hypotension could be almost eliminated, but at the cost of reactive hypertension. [10,19] Subsequent work with lowerdose phenylephrine infusions supported prophylactic infusions as part of routine CS. [14] Further dosefinding studies suggested that a range of 25 50 µg/min seemed to give the most benefit with the fewest sideeffects.…”
Section: Vasopressor Management Strategiesmentioning
confidence: 99%